Accounting conservatism and firms' performance: evidence from Malaysian listed firms. (11th April 2023) - Ur-Rehman, Saif; Khan, Faisal; Hemdan, Dalia Ali Mostafa; Khan, Hashim
Accounting conservatism is a mechanism used to develop a true and fair view of financial statements which relies significantly on factors affecting the finance managers in formulating conservative policy. Methodologically, two approaches have been adopted to collect the primary and secondary data of Malaysian listed firms. Findings indicate that external auditors' influence, audit committee influence and stock market uncertainty are main predictors well-supported by primary and secondary data to determine the degree of conservatism at firm level. It is empirically evident that three of the five factors are affecting the conservative accounting policy among Malaysian firms.